Natural Resources and Violent Conflict : Options and Actions - Bannon, Ian (Washington, DC: World Bank, 2013)
Recent research undertaken by the Bank and others, suggest that developing countries face substantially higher risks of violent conflict, and poor governance if highly dependent on primary commodities. Revenues from the legal, or illegal exploitation of natural resources have financed devastating conflicts in large numbers of countries across regions. When a conflict erupts, it not only sweeps away decades of painstaking development efforts, but creates costs and consequences-economic, social, political, regional-that live on for decades. The outbreak of violent domestic conflict amounts to a spectacular failure of development-in essence, development in reverse. Even where countries initially manage to avoid violent conflict, large rents from natural resources can weaken state structures, and make governments less accountable, often leading to the emergence of secessionist rebellions, and all-out civil war. Although natural resources are never the sole source of conflict, and do not make conflict inevitable, the presence of abundant primary commodities, especially in low-income countries, exacerbates the risks of conflict and, if conflict does break out, tends to prolong it and makes it harder to resolve. As the Governance of Natural Resources Project (a research project) took shape, the discussion moved toward practical approaches and policies that could be adopted by the international community. This book presents the papers commissioned under the Governance of Natural Resources Project, offering a rich array of approaches and suggestions that are feeding into the international policy debate, and hopefully lead, over time to concerted international action, to help developing countries better manage their resource wealth, and turn this wealth into a driver of development rather than of conflict.